Mechanisms on chemotherapy resistance of colorectal cancer stem cells and research progress of reverse transformation: A mini-review - Chen, Lei; Yang, Funing; Chen, Si; Tai, Jiandong (Frontiers in Medicine, 2022)
Tumor recurrence and chemotherapy resistance are mainly responsible for poor prognosis in colorectal cancer (CRC) patients. Cancer stem cell (CSC) has been identified in many solid tumors, including CRC. Additionally, CSC cannot be completely killed during chemotherapy and develops resistance to chemotherapeutic drugs, which is the main reason for tumor recurrence. This study reviews the main mechanisms of CSC chemotherapy resistance in CRC, including activation of DNA damage checkpoints, epithelial-mesenchymal transition (EMT), inhibition of the overexpression of antiapoptotic regulatory factors, overexpression of ATP-binding cassette (ABC) transporters, maintenance of reactive oxygen species (ROS) levels, and the dormant state of CSC. Advances in research to reverse chemotherapy resistance are also discussed. Our study can provide the promising potential for eliminating CSC and preventing tumor progression for CRC treatment.